Effect of Geometry Modifications on the Vectoring Performance of a Controlled Jet - M. N. Tomac (Journal of Applied Fluid Mechanics, 2017)
Jet vectoring performances of ten different designs with various depths and geometrical outlines were quantified through constant temperature anemometry measurements for a Reynolds number range from 10,000 to 30,000 by using passive and active flow control methods at cold flow. The reference design was based on NASA’s double throat nozzle concept and a self-injection double throat nozzle design that uses similar flow control concept as the reference design, were also tested for performance comparison. Furthermore, jet vectoring performance of a single throat design, utilizing Coanda effect for jet vectoring, was also quantified. Results indicated jet vectoring angles starting from 2° up to 47° for a control jet flow rate range from 1% up to 10% with respect to the primary jet flow rate in the investigated Re range. Maximum jet vectoring angle was achieved with a single throat design which incorporates small step geometry before the Coanda surface for more effective flow attachment and these results were compared with the vectoring performance of the double throat nozzle designs.